2011
DOI: 10.1111/j.1365-2133.2011.10209.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, multicentre study of directed daylight exposure times of 1½ vs. 2½ h in daylight-mediated photodynamic therapy with methyl aminolaevulinate in patients with multiple thin actinic keratoses of the face and scalp

Abstract: Daylight-mediated MAL-PDT is an effective, convenient and nearly pain-free treatment for patients with multiple thin AKs. Daylight-mediated PDT procedures were easily performed and 2 h of daylight exposure resulted in uniformly high response rates when conducted in the period from June to October in Nordic countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
191
4
18

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(225 citation statements)
references
References 27 publications
12
191
4
18
Order By: Relevance
“…Although patients enrolled in the Australian study had individual lesions treated,13 the expert panel agreed that daylight PDT is recommended for use in patients who require field therapy (i.e., large areas of actinic damage) to treat visible lesions and subclinical disease, depending on the clinical need. This is consistent with current guidelines for treatment of AK7 and is supported by findings from the studies of daylight PDT (including field treatment) in northern Europe 11, 14, 15, 16…”
Section: Whom To Treat With Daylight Pdt With Methyl Aminolevulinate supporting
confidence: 90%
See 4 more Smart Citations
“…Although patients enrolled in the Australian study had individual lesions treated,13 the expert panel agreed that daylight PDT is recommended for use in patients who require field therapy (i.e., large areas of actinic damage) to treat visible lesions and subclinical disease, depending on the clinical need. This is consistent with current guidelines for treatment of AK7 and is supported by findings from the studies of daylight PDT (including field treatment) in northern Europe 11, 14, 15, 16…”
Section: Whom To Treat With Daylight Pdt With Methyl Aminolevulinate supporting
confidence: 90%
“…The efficacy and safety of daylight PDT with MAL in the treatment of AK has been assessed in four randomised trials conducted in Europe11, 14, 15, 16, 17 and one randomised controlled trial conducted in Australia 13. The European trials consisted of a small exploratory study comparing daylight PDT with c‐PDT,11 two comparative studies with different concentrations of MAL cream16 and daylight exposure times14, 15 and, most recently, a phase III randomised trial comparing daylight PDT with c‐PDT (only preliminary results reported) 17.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations